2017
DOI: 10.1073/pnas.1614781114
|View full text |Cite
|
Sign up to set email alerts
|

SIR2 suppresses replication gaps and genome instability by balancing replication between repetitive and unique sequences

Abstract: Replication gaps that persist into mitosis likely represent important threats to genome stability, but experimental identification of these gaps has proved challenging. We have developed a technique that allows us to explore the dynamics by which genome replication is completed before mitosis. Using this approach, we demonstrate that excessive allocation of replication resources to origins within repetitive regions, induced by SIR2 deletion, leads to persistent replication gaps and genome instability. Converse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 35 publications
4
50
0
Order By: Relevance
“…Analyses of our S-phase Sort-Seq data revealed that Sir2 had a detectable effect on the replication progression of euchromatic origins, with later-euchromatic origins falling further behind both early-euchromatic origins and telomeric-X origins in sir2 Δ cells ( Figure 5 D ). These effects might be relevant to the inability to complete the duplication of late-replicating euchromatin by early-G2 phase in sir2 Δ cells as documented in (31). Therefore, the euchromatic- and telomeric-X origin cohorts were assessed using the data sets from this previous study.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Analyses of our S-phase Sort-Seq data revealed that Sir2 had a detectable effect on the replication progression of euchromatic origins, with later-euchromatic origins falling further behind both early-euchromatic origins and telomeric-X origins in sir2 Δ cells ( Figure 5 D ). These effects might be relevant to the inability to complete the duplication of late-replicating euchromatin by early-G2 phase in sir2 Δ cells as documented in (31). Therefore, the euchromatic- and telomeric-X origin cohorts were assessed using the data sets from this previous study.…”
Section: Resultsmentioning
confidence: 98%
“…Specifically, in sir2 Δ cells, the rDNA origins (r-ORIGIN) are more active, and because there are so many, limiting S-phase MCM complex activation factors get sequestered away from euchromatic origins causing a delay in euchromatic-origin activation. This sir2 Δ-caused sequestration of S-phase MCM complex activation factors contributes to the incomplete duplication of late replicating regions in G2 phase (31). In support of this model, sir2 Δ cells harboring a mutation within the rDNA origin, referred to here as r-origin* , reduces rDNA-dependent sequestration of S-phase MCM complex activation factors and partially rescues the delayed replication of late regions caused by sir2 Δ.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, instability at the ribosomal DNA (rDNA) locus, which contains ~100-200 tandemly repeated copies in the genome, can result in the formation of rDNA extra-chromosomal circles (ERCs), and is is a major determinant of yeast replicative lifespan (RLS) [11][12][13][14][15] . A single nucleotide polymorphism that reduces the rate of origin firing at the rDNA locus increases rDNA stability, and thereby increases RLS [16,17] . In a seemingly unrelated pathway, a decrease in vacuolar acidity early in a mother cell's life promotes mitochondrial dysfunction and limits her lifespan [7] .…”
Section: Introductionmentioning
confidence: 99%